Modelo para determinar las percepciones respecto al aporte que tienen las marcas de la línea de productos lácteos de consumo masivo en la calidad de vida de las personas de clase media de la Parroquia de Turubamba del sector Sur de la Ciudad de Quito. - Suntaxi Paucar, Deysi Susana (2013)
In order to develop the model investigation of the concepts related to the subject was made, it is also necessary to visit the area to gather information, and thus to choose the most appropriate tool for such development. Note how it influences the perception in humans.